2021
DOI: 10.3390/pathogens10030381
|View full text |Cite
|
Sign up to set email alerts
|

Amplicon Sequencing of Variable 16S rRNA from Bacteria and ITS2 Regions from Fungi and Plants, Reveals Honeybee Susceptibility to Diseases Results from Their Forage Availability under Anthropogenic Landscapes

Abstract: European Apis mellifera and Asian Apis cerana honeybees are essential crop pollinators. Microbiome studies can provide complex information on health and fitness of these insects in relation to environmental changes, and plant availability. Amplicon sequencing of variable regions of the 16S rRNA from bacteria and the internally transcribed spacer (ITS) regions from fungi and plants allow identification of the metabiome. These methods provide a tool for monitoring otherwise uncultured microbes isolated from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 83 publications
2
19
0
Order By: Relevance
“…However, some confusion could arise as a result of the relatively high percentages of unclassified tags which varied approximately between 94% and 98%. A high percentage of unclassified fungi when ITS-based methods are employed is not unusual and could be explained by the incompleteness of the international databases with data of environmental samples [8,19,40]. For example, it varies from above 50% to 80% for environmental samples [40][41][42] to "significant" [43] and above 98% [44] for fermented foods and products.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some confusion could arise as a result of the relatively high percentages of unclassified tags which varied approximately between 94% and 98%. A high percentage of unclassified fungi when ITS-based methods are employed is not unusual and could be explained by the incompleteness of the international databases with data of environmental samples [8,19,40]. For example, it varies from above 50% to 80% for environmental samples [40][41][42] to "significant" [43] and above 98% [44] for fermented foods and products.…”
Section: Discussionmentioning
confidence: 99%
“…Because the microbial composition of the honeybees' microbiomes, as well as those of the honeybee products, is strongly influenced by the landscape and anthropogenic pressure [19], we decided to investigate the fungal composition in bee bread at the end of June 2020 in four different locations in Bulgaria (Figure 1). This period was chosen as one of the most active concerning the honeybees' foraging activities while the locations were selected because of the different degrees of anthropogenic pressure, as well as the landscape and the climatic features.…”
Section: Introductionmentioning
confidence: 99%
“…Alteration of gut microbiota influences host metabolism and may affect the storage of energy in honeybees. Some studies had suggested that changes in diversity of gut microbiota are associated with some diseases and opportunistic bacteria 43 , included fungal pathogens and neogregarines 21 . This would benefit honeybees to reduce parasite and pathogenic infection for successful overwintering 24 .…”
Section: Discussionmentioning
confidence: 99%
“…During the growth stage of honeybees, the intestinal bacteria are also involved in growth improvement and immunomodulation of its hosts 15 , 19 . The intestinal bacteria of a healthy honeybees are characterized by its dynamic stability 21 . However, it can show dysbiosis or disequilibrium when challenged by many factors alone or combination, such as a different diet 22 , pesticide exposure 23 , parasite and pathogen infection 24 , and behavioral tasks 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, since this is an active research area, several studies (such as Ptaszyńska et al, 2021 64 ) were added throughout our analysis that would have fulfilled inclusion criteria. This underlines the importance of a curated and active database as proposed by Engel et al We intend to include all studies published since the initial search in a later iteration of this study.…”
Section: Limitationsmentioning
confidence: 99%